1976
DOI: 10.1002/zaac.19764190307
|View full text |Cite
|
Sign up to set email alerts
|

Nebenreaktionen bei der Umsetzung von Trimethylsilylazid mit Trimethylphosphit und Trisdimethylaminophosphin

Abstract: Trisdimethylaminophosphin reagiert mit Trimethylsilylazid unter Stickstoffentwicklung und Bildung von N‐Trimethylsilyl‐iminophosphorsäurehexamethyltriamid, (Me2N)3PNSiMe3. Unter Eliminierung von Dimethylamino‐trimethylsilan bildet sich daneben das Diphosphazen (Me2N)3PNP(NMe2)2NSiMe3. Die Umsetzung von Trimethylphosphit mit Trimethylsilylazid liefert neben dem erwarteten N‐Trimethylsilyl‐iminophosphorsäuretrimethylester, (MeO)3PNSiMe3, den isomeren N‐Trimethylsilyl‐N‐methyl‐aminophosphorsäuredimethyles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Whereas (Me 2 N) 3 P=N–N=N‐SiMe 3 eliminates N 2 at room temperature, phosphazides bearing cyclic amino substituents require heating. Schlak et al reported that a considerable amount of hardly separable P 2 ‐byproduct (Me 2 N) 3 P=N–P(NMe 2 ) 2 =N–SiMe 3 is formed in the course of the Staudinger reaction of (MeN 2 ) 3 P . We find, that analogous side products are only observed in trace amounts in our compounds with pyrrolidino, piperidino, or azepanyl groups (Scheme ).…”
Section: Resultssupporting
confidence: 55%
“…Whereas (Me 2 N) 3 P=N–N=N‐SiMe 3 eliminates N 2 at room temperature, phosphazides bearing cyclic amino substituents require heating. Schlak et al reported that a considerable amount of hardly separable P 2 ‐byproduct (Me 2 N) 3 P=N–P(NMe 2 ) 2 =N–SiMe 3 is formed in the course of the Staudinger reaction of (MeN 2 ) 3 P . We find, that analogous side products are only observed in trace amounts in our compounds with pyrrolidino, piperidino, or azepanyl groups (Scheme ).…”
Section: Resultssupporting
confidence: 55%
“…The protocol of Staudinger represents the most efficient and nowadays preferably used pathway to a variety of iminophosphoranes. [21,22,23,24] However, it should be kept in mind that the use of sensitive azides is always hazardous due to violent decompositions [25] which is particularly true for hydrazoic acid (HN 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…further explored properties of (dimethylamino)iminophosphoranes 3 and reported on the first entirely dialkylamino substituted diphosphazene (Me 2 N) 3 P=N−P(NMe 2 ) 2 =N−SiMe 3 ( 7 , Scheme 2 ). [24] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anlaû zu dieser Hoffnung gibt uns auch die isoelektronische Beziehung der beiden funktionellen Baueinheiten [M=N=P t Bu 3 ] und [M=O=Si t Bu 3 ]. Letzterer ¹Siloxª-Ligand wurde von Weidenbruch [6] und Wolczanski sehr erfolgreich in der Chemie niederkoordinierter, d-elektronenarmer Ûbergangsmetallkomplexe eingesetzt, so etwa zur Stabilisierung der dreifach-koordinierten, extrem reak- [17], TaOCl 3 [18], (Me 2 N) 3 P=NSiMe 3 [19], Me 3 SiN=PPh 3 [20], Me 3 SiN=P t Bu 3 [21].…”
Section: Introductionunclassified